If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 25b + -16 = 3(6b + -5) Reorder the terms: -16 + 25b = 3(6b + -5) Reorder the terms: -16 + 25b = 3(-5 + 6b) -16 + 25b = (-5 * 3 + 6b * 3) -16 + 25b = (-15 + 18b) Solving -16 + 25b = -15 + 18b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-18b' to each side of the equation. -16 + 25b + -18b = -15 + 18b + -18b Combine like terms: 25b + -18b = 7b -16 + 7b = -15 + 18b + -18b Combine like terms: 18b + -18b = 0 -16 + 7b = -15 + 0 -16 + 7b = -15 Add '16' to each side of the equation. -16 + 16 + 7b = -15 + 16 Combine like terms: -16 + 16 = 0 0 + 7b = -15 + 16 7b = -15 + 16 Combine like terms: -15 + 16 = 1 7b = 1 Divide each side by '7'. b = 0.1428571429 Simplifying b = 0.1428571429
| 8u=4v-32 | | -3x+5+6x=-10 | | x+62+x+62+70=180 | | 9v^-2/3=16 | | 4(x-5)=-5 | | 3n+5+5n-6= | | X-5/6-1=x-8/7 | | -4x+4y=-28 | | (12/7)=6y | | 11x-5+8x+90=180 | | 5(4-16)=20 | | 4x+5y=-76 | | 63x+9=-36 | | (6/7)*v=42 | | 105=23x+1+11x+2 | | 20x^4-20x^2+3=0 | | 5u+5=-10 | | 3x+5y=-67 | | 4+5m=12+3m | | 12x^3-12x^2+8=0 | | (X/15)=15 | | x+70+75+x+45=180 | | 2(x-4)=3x+32 | | 20a+13b+6c+6c-6b-4a= | | -3x-y=26 | | (y^1/8)=-1 | | 63x+9=36 | | 2t-11=15 | | -3x+3y=30 | | 15x-3=8x+16+44 | | cotg4x/cotg3x | | 8u=4v-34 |